Vpliv kakovosti vhodnih podatkov na kakovost ortofota : Influence of Input Data Quality on the Quality of Orthophoto - Mojca Kosmatin Fras (Geodetski Vestnik, 2004)
In the article, the influence of input data for orthophoto map production on the final product is discussed. The quality of orthophoto is mostly influenced by image orientation parameters, quality of the digital elevation model and digital image quality. A short description of orthophoto production procedure is given, and the input data and their impact on the product is treated in more detail. The undestanding of this topic is highly relevant for a correct use of the orthophoto.